What It’s Like to Ride a Bike: Understanding Cyclist Experiences - Scott, Georgia Clare (Curtin University, 2018)
Cyclists can make important contributions to transport policy, if only we ask them. This thesis explores how people experience cycling in three case study cities – Perth, Melbourne and Utrecht. Cyclists were recruited for semi-structured and go-along interviews. The key findings indicate that the combination of traditional and mobile methods yield valuable information for developing understandings of the embodied experience of cycling, which can be used to inform policy and guide the creation of sustainable cities.